The application of the improved 3D rat testicular cells co-culture model on the in vitro toxicity research of HZ1006. (3rd September 2019) - Zhang, Xiaofang; Zhu, Yuping; Tian, Yijun; Yan, Han; Ren, Lijun; Shi, Wenjing; Zhu, Jiangbo; Zhang, Tianbao
Abstract: The aims of the present research are to further validate the application of the improved three-dimensional (3 D) rat testicular cell co-culture model to evaluate the effects of various reprotoxic chemicals on the function of the main somatic cells, as well as on spermatogonial cell differentiation and even spermatogenesis, and to investigate the specific toxicant mechanisms in testes treated with HZ1006, a hydroxamate-based a hydroxamate-based histone deacetylase inhibitor (HDACI). Based on the characteristics of HZ1006, the appropriate exposure duration (8, 16, or 24 days), dosage (0, 3.125, 6.25, 12.5, or 25 μM) and toxic endpoints suitable for detection were selected in the experiments. The results showed inhibition of cell proliferation, reduced testosterone levels, and decreased spermatogonial cell meiosis-specific gene expression, as well as decreased protein levels of androgen receptor (AR) and decreased expression of the AR target gene PSA, accompanied by inhibition of Hdac6 expression after HZ1006 exposure in the 3 D rat testicular cell co-culture model. These findings indicate that the improved 3 D rat testicular cell co-culture model we have established has the potential to become a new testicular toxicity test system that can be used to test toxic characteristics and mechanisms of new compounds and has good application prospects, although more research on the model is required.